Linear Analysis of Stability of Pitched Roof Frames - BOCOVO, T. Mariano; GBAGUIDI AÏSSE, GÉRARD LÉOPOLD; DEGAN, GÉRARD (My University, 2018)
In this paper, geometric nonlinear analysis of pitched roof frames was carried out by the stiffness matrix method using stability functions. The analysis focused on four frames; the obtained results show that the increase in the inclination of the crossbar makes it possible to take full advantage of the “arch effect”. Arch effect is due to the presence of crossbars which have a linear arch shape. Furthermore, the angle as well as the length ratio, between the crossbar and post, influence critical load value.
Keywords: Geometric nonlinear analysis; Stiffness matrix method; Stability functions; Determinant; Buckling load; Pitched roof